PCIF1 drives oesophageal squamous cell carcinoma progression via m6Am‐mediated suppression of MTF2 translation - Kang Li; Yuxuan Yi; Rongsong Ling; Caihua Zhang; Zhihui Zhang; Yue Wang; Ganping Wang; Jie Chen; Maosheng Cheng; Shuang Chen (Clinical and Translational Medicine)
Abstract Oesophageal squamous cell carcinoma (OSCC) represents a highly aggressive malignancy with limited therapeutic options and poor prognosis. This study uncovers PCIF1 as a critical driver of OSCC progression via m6Am RNA modification, leading to translational repression of the tumour suppressor MTF2. Our results demonstrate that PCIF1 selectively suppresses MTF2 translation, activating oncogenic pathways that promote OSCC growth. In vitro and in vivo models confirm that PCIF1 knockdown reduces OSCC progression, whereas MTF2 knockdown counteracts this effect, highlighting the importance of the PCIF1‐MTF2 axis. Clinical analyses further reveal that high PCIF1 expression and low MTF2 expression correlate with advanced tumour stage, poor treatment response and decreased overall survival. Furthermore, in a preclinical mouse model, PCIF1 knockout enhanced the efficacy of anti‐PD1 immunotherapy, reducing tumour burden and improving histological outcomes. Notably, flow cytometry analysis indicated that PCIF1 primarily exerts its effects through tumour‐intrinsic mechanisms rather than direct modulation of the immune microenvironment, distinguishing its mode of action from PD1 blockade. These findings establish PCIF1 and MTF2 as promising prognostic markers and therapeutic targets for OSCC, offering new avenues for treatment strategies and patient stratification. Key points PCIF1 promotes OSCC progression via m6Am methylation at the MTF2 mRNA 5′ cap. m6Am methylation suppresses MTF2 translation, enhancing tumour cell proliferation and invasion. Targeting PCIF1 holds therapeutic potential for OSCC treatment.